Stability evaluation of ethanol dry reforming on Lanthania‐doped cobalt‐based catalysts for hydrogen‐rich syngas generation - Fahim, Fayaz; Long, Giang Bach; Mahadi, Bahari; Trinh, Duy Nguyen; Khanh, B. Vu; Ramesh, Kanthasamy; Chanatip, Samart; Chinh, Nguyen‐Huy; Dai‐Viet, N. Vo (Wiley Online Library, 2019)
Catalytic stability with time‐on‐stream is an important aspect in ethanol dry reforming (EDR) since catalysts could encounter undesirable deterioration arising from deposited carbon. This work examined the promotional effect of La on 10%Co/Al2O3 in terms of activity, stability, and characteristics. Catalysts were characterized by X‐ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), Raman, and X‐ray photoelectron spectroscopy (XPS) measurements whilst catalytic EDR performance of La‐promoted and unpromoted 10%Co/Al2O3 prepared via wet impregnation technique was investigated at 973 K for 72 h using a stoichiometric feed ratio (C2H5OH/CO2 = 1/1). La promoter substantially enhanced both metal dispersion and metal surface area from 0.11% to 0.64% and 0.08 to 0.43 m2 g−1, respectively. Ethanol and CO2 conversions appeared to be stable within 50 to 72 h after experiencing an initial activity drop. The conversion of C2H5OH and CO2 for La‐promoted catalyst was about 1.65 and 1.34 times greater than unpromoted counterpart in this order. The carbonaceous deposition was considerably decreased from 55.6% to 36.8% with La promotion due to La2O2CO3 intermediate formation. Additionally, 3%La‐10%Co/Al2O3 possessed greater oxygen vacancies acting as active sites for CO2adsorption and hence increasing carbon gasification. Even though graphitic and filamentous carbons were formed on used catalyst surface, La‐addition diminished graphite formation and increased the reactiveness of amorphous carbon.